Novel molecule combinations and corresponding hybrids targeting artemisinin-resistant Plasmodium falciparum parasites. (1st May 2021) - Ouji, Manel; Nguyen, Michel; Mustière, Romain; Jimenez, Tony; Augereau, Jean-Michel; Benoit-Vical, Françoise; Deraeve, Céline
Graphical abstract: Abstract: Malaria is still considered as the major parasitic disease and the development of artemisinin resistance does not improve this alarming situation. Based on the recent identification of relevant malaria targets in the artemisinin resistance context, novel drug combinations were evaluated against artemisinin-sensitive and artemisinin-resistant Plasmodium falciparum parasites. Corresponding hybrid molecules were also synthesized and evaluated for comparison with combinations and individual pharmacophores (e.g. atovaquone, mefloquine or triclosan). Combinations and hybrids showed remarkable antimalarial activity (IC50  = 0.6 to 1.1 nM for the best compounds), strong selectivity, and didn't present any cross-resistance with artemisinin. Moreover, the combination triclosan + atovaquone showed high activity against artemisinin-resistant parasites at the quiescent stage but the corresponding hybrid lost this pharmacological property. This result is essential since only few molecules active against quiescent artemisinin-resistant parasites are reported. Our promising results highlight the potential of these combinations and paves the way for pharmacomodulation work on the best hybrids.